P53 An analysis of service users accessing a routine contraception service via an online platform during the COVID-19 pandemic. (16th June 2022) - Goward, Charlotte; Clune, Mark; Ebbutt, Kate; Perera, Sean
Abstract : Introduction: The COVID-19 pandemic has moved some health services, such as contraception, online. Eleven local authorities in London enrolled for a routine contraception (RC) e-service. After completing an online, asynchronous consultation, RC could be delivered or collected in pharmacy. Method: Retrospective analysis of 10, 525 RC consultations completed between 1st January 2021 and 31st December 2021, from 11 local authorities in London. Age, ethnicity and deprivation decile were used to identify demographic trends. Results: The majority of RC consultations were completed by 25-34 year olds (47.9%, n=5042). The majority (61.2%, n=6442) of consultations were completed by users in the lower deciles 2-4. 66.7% (n=7021) of consultations were completed by users from ethnic minority groups. In 16-17 year olds and 35-44 year olds, the majority of RC consultations were completed by users in the bottom 3 deciles of deprivation (55.5% (n=146) and 55.8% (n=383) respectively). 68% (n=607) of Black African women were from the bottom 3 deciles of deprivation, as were 59.5% (n=606) of Black Caribbean women as compared to 40.6% (n1432) of White British women. 46.1% (n=412) of Black African women, 51.9% (n=576) of Black Caribbean women, and 45.5% (n=1595) of White British women, were 16-24 years old. Discussion: The majority of individuals accessing RC online are young and racially minoritised, experiencing significant levels of deprivation. An online RC service can reach populations with the poorest sexual health outcomes, reduce unintended pregnancies and help reduce health inequalities. Local authorities could consider whether an online RC service would help in their area.